Nonlinearity-controllable all-optical logic gates based on broadband defect mode - Liu, Bin; Tian, Huiping; Lu, Hui; Ji, Yuefeng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
To avoid the adverse effect of unstable nonlinear progress on the design of all-optical logic gates, the broadband defect mode of one-dimensional photonic crystal with dual-defects has been studied. By using transfer matrix method, influences of period number and refractive indices on crystal’s transmission spectrum are analyzed. It is pointed out that with proper parameters, broadband defect mode, which could be used to reduce the influence between the nonlinear refractive index and field distribution, can be gained. Due to this fact, the designed XOR, AND and NOT logic gates can be steadily controlled with low-threshold and high-contrast.
Optica Applicata, Vol. 40, 2010, nr 3, s. 657-668
Keywords: optyka; photonic crystals; all-optical logic gates; broadband defect mode; nonlinearity